Media and journalism training in Vanuatu - Mandavah, Dave (Pacific Journalism Review : Te Koakoa, 2017)
Commentary: In 2009, a two-year diploma course in Journalism and Media began at the Vanuatu Institute of Technology. It was the first full time journalism and media course in the country and was long overdue as the local media industry expanded. It is the only diploma level course offered at the VIT. The Pacific Media and Communications Facility was established at VIT seven years ago as part of an AusAID initiative, managed by MDI International in association with MC Media and Associates. Work in the facility served as the basis of the two-year diploma course. It provided a foundation for more than 30 graduates, many of whom are now employed in the burgeoning media industry in Vanuatu. This commentary traces the background and development of this programme.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnYyM2kyLjMzNg